Gender Differences Related to Lifestyle Behaviour of University Students (Baltic Journal of Sport and Health Sciences, 2019)
Background. A healthy lifestyle is the one of the most relevant subjects in a modern society comprising three factors – healthy diet, sufficient physical activity, and absence of harmful habits (Strukčinskienė et al., 2014). It has been pointed out that healthy lifestyle behavioural patterns contribute to the prevention of diabetes mellitus type II, cardiovascular, and oncological diseases (Javtokas et al., 2014).Studies performed in different countries have discovered that students’ dietary habits do not correspond to the recommendations of the World Health Organization on healthy diet (Akhtar Zareen, & Sarmad, 2018; Česnavičienė, Proškuvienė, & Motiejūnaitė, 2015). In their study, Sigmundova, Chmelik, Sigmund, Feltlova, & Frömel (2013) found that the lowest level of physical activity was reached by only two thirds of students.  The prevalence of harmful habits was also very high: more than half of students used tobacco during the last 12 months, and about 92% of students used alcohol over the last year (Dobrovolskij & Stukas, 2014).Literature review revealed that recently a number of studies analysing students’ lifestyle patterns were performed, however, there is still a lack of studies on lifestyle behaviour among the Lithuanian Sports University students.Methods. Questionnaires and statistical analysis.Results. The results showed that meat consumption was indicated by twice more males than females (p < .05). More males consumed ice cream, while yoghurt was preferred more frequently by females (p < .05). Fried potatoes were used more frequently by males (p < .05). With the respect to sedentary lifestyle, high intensity activity and moderate intensity activity, there were no differences between males and females, however, more females than males walked (p < .05). Beer consumption was more prevalent between males while wine consumption was more common between females (p < .05).